The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jfe.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the poor: Taxation of marketed forest products in developing countries

Abstract: In this article, we investigate whether taxation of households' production of marketed forest products in developing countries is likely to assist in achieving the general development objectives of resources conservation and poverty alleviation. Based on an empirical study on such taxation in a village in Tanzania, we develop and solve a theoretical analytical model to analyse taxation, when households' access to alternative income generating opportunities is heterogeneous. Findings are that taxation adversely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…The conclusions are similar to the theoretical, integrated integrated agriculture and forestry model used by Anthon et al (2008) which concluded that public forest policy, biased towards environment conservation, affect the economies of forest based communities and has the greatest impact on the poorest households. There are no similar studies in Nepal that could be used to directly compare the findings of this study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The conclusions are similar to the theoretical, integrated integrated agriculture and forestry model used by Anthon et al (2008) which concluded that public forest policy, biased towards environment conservation, affect the economies of forest based communities and has the greatest impact on the poorest households. There are no similar studies in Nepal that could be used to directly compare the findings of this study.…”
Section: Discussionsupporting
confidence: 80%
“…Accounting for household economic heterogeneity and levels of dependency of users is crucial for a robust understanding of the economic effects of changes in the management of common property resources (Baland and Platteau, 1999). Anthon et al (2008) developed a model that includes household economic heterogeneity, and integrated agriculture and forestry components to explain economic impact of public forest policy changes on farming communities in developing countries. However, their model is theoretical, not empirical, and could not be used to evaluate the impacts of different policy scenarios.…”
Section: Similar Issues Have Arisen In Other Countriesmentioning
confidence: 99%
“…For these communities, 46 ecosystem final services benefits in the form of NTFPs provide a 47 source of complementary cash income, or a safety net when 48 agricultural yields are low (Anthon et al, 2008;Ngaga et al, 2009). 49 In addition to timber extraction, the production of building poles, 50 charcoal and firewood has led to overexploitation of forests and is 51 one of the main immediate drivers (alongside agricultural 52 expansion) of forest degradation and deforestation in Tanzania 53 (Hofstad, 1997;Chiesa et al, 2009;Ahrends et al, 2010;URT, 54 2010).…”
Section: Q2mentioning
confidence: 99%
“…Charcoal production takes place in rural areas. In the lower 300 woodland and forest areas of the EAM, charcoal production is 301 practised for commercial purposes, mainly by men (Luoga et al, 302 2000;Anthon et al, 2008). Local communities are seasonally or 303 occasionally involved in charcoal production, primarily outside 304 planting and harvesting seasons.…”
mentioning
confidence: 99%
“…This high demand increases the number of harvested plant species, which in turn can modify species composition and diversity (Bengtsson et al, 2000). Achieving sustainable use of forest products, where the annual rates of extraction do not exceed the annual increments, is particularly challenging where poverty prevails (Anthon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%